2013
DOI: 10.5267/j.msl.2013.06.037
|View full text |Cite
|
Sign up to set email alerts
|

The role of cultural intelligence of managers in promoting employees’ collaboration

Abstract: Collaboration can be a very challenging process precisely because it is a highly intense way of working, requiring new ways of thinking, behavior and ways of operating. Cultural Intelligence (CI) is an antecedent for collaboration. The primary goal of this survey is to investigate the relationship between cultural intelligence of managers and their employees' collaboration. This research is a descriptive-correlation study where 119 managers and 175 employees are selected by stratified random sampling from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The results of structural equation modeling showed that cultural intelligence had a significant effect on selfesteem and marital conflict resolution styles. These results are in line with the findings of Zartoshtiyan and Gholamipour [9] and Ahmadi et al [10] who demonstrated the significant association between cultural intelligence and conflict resolution styles. Moreover, the results are in line with the findings of Ozsoy [7] and Reguieg [8] who showed a positive relationship between the dimensions of conflict resolution styles and personality, emotional intelligence abilities, and cultural intelligence.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of structural equation modeling showed that cultural intelligence had a significant effect on selfesteem and marital conflict resolution styles. These results are in line with the findings of Zartoshtiyan and Gholamipour [9] and Ahmadi et al [10] who demonstrated the significant association between cultural intelligence and conflict resolution styles. Moreover, the results are in line with the findings of Ozsoy [7] and Reguieg [8] who showed a positive relationship between the dimensions of conflict resolution styles and personality, emotional intelligence abilities, and cultural intelligence.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown a positive relationship between the dimensions of conflict resolution styles and personality, emotional intelligence, and cultural intelligence [7,8]. There is a significant relationship between cultural intelligence and conflict resolution techniques [9,10]. Also, Yeke and Semercioz found a significant relationship between personality traits and cultural intelligence with communication abilities [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A positive environment in a diverse team is proven to increase organizational commitment and job performance (Chen et al, 2011a; Iskhakova and Ott, 2020). CI of managers also fosters collaboration among employees (Ahmadi et al, 2013). Performance, cultural adaptation and collaboration are necessary for a virtual team effectiveness as cross-cultural and team collaboration challenges are highly reflected in the virtual teams’ literature (Kayworth and Leidner, 2000; Szewc, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals, having higher CQ, may show stronger cultural competitiveness, and their cognitive, behavioral and motivational capacities make them work effectively with other members who have 1479 Beyond national culture difference different cultures as well as adjust quickly to unfamiliar settings (Ott and Michailova, 2018). According to Ahmadi et al (2013), cultural intelligence is a significant antecedent for collaboration. Since the formation of this construct and the establishment of Cultural Intelligence Scale (CQS) (Ang et al, 2007), empirical research with regard to CQ, though still limited, continuously flourishes in multiple disciplines (Sharma and Hussain, 2017).…”
Section: Cultural Intelligence (Cq)mentioning
confidence: 99%